Uji Aktivitas Antioksidan dan Profil Kandungan Fenol serta Flavonoid pada Ekstrak Daun Sirsak (Annona muricata L.) - Juliana Sihombing; Muhammad Yunus; Finna Piska (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Free radicals are unstable molecules that can trigger oxidative stress and contribute to various degenerative diseases. Antioxidants play an important role in neutralizing free radicals by donating electrons, thereby preventing cellular damage. Soursop leaves (Annona muricata L.) are one type of plant that contains secondary metabolite compounds with high potential as natural antioxidants, especially phenolic and flavonoid compounds. This study aims to determine the antioxidant activity, total phenolic content, and total flavonoid content of the ethanol extract of soursop leaves. Plant extraction was carried out by maceration using 96% ethanol. The determination of total phenolic and flavonoid contents using Folin–Ciocalteu reagent and AlCl₃, respectively, yielded values of 66.03762169 mg GAE/g and 21.105064 mg QE/g, indicating that the phenolic and flavonoid contents were classified as high.